2010
DOI: 10.1063/1.3355199
|View full text |Cite
|
Sign up to set email alerts
|

Density approach to ballistic anomalous diffusion: An exact analytical treatment

Abstract: This paper addresses the problem of deriving the probability distribution density of a diffusion process generated by a nonergodic dichotomous fluctuation using the Liouville equation (density method). The velocity of the diffusing particles fluctuates from the value of 1 to the value of −1, and back, with the distribution density of time durations τ of the two states proportional to 1/τμ in the asymptotic time limit. The adopted density method allows us to establish an exact analytical expression for the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…and ξ〉 is the average of ξ(t) so that ξ t ( ) takes the values ±1. The above equation has been intensively studied, and a general solution for the probability distribution P(W, t) generated by a generic waiting time distribution can be found in literature 17 . Knowing the distribution we may evaluate the first passage time distribution in reaching the necessary level of technology to e.g.…”
Section: Open Model and Resultsmentioning
confidence: 99%
“…and ξ〉 is the average of ξ(t) so that ξ t ( ) takes the values ±1. The above equation has been intensively studied, and a general solution for the probability distribution P(W, t) generated by a generic waiting time distribution can be found in literature 17 . Knowing the distribution we may evaluate the first passage time distribution in reaching the necessary level of technology to e.g.…”
Section: Open Model and Resultsmentioning
confidence: 99%
“…We employ the same procedure followed in the calculation of ξ S . Bologna et al [29], as well as Akimoto [30], demonstrated that the resulting distribution is a skewed Lamperti dis-…”
Section: Establishing Complexity Management With Time Rather Thanmentioning
confidence: 98%
“…This can be directly checked using the distribution derived by Lamperti [ 31 , 32 ], and which describes the distribution associated with Equation ( 15 ) for . Integrating Equations ( 32 ) and (33) the result with respect to time, we obtain …”
Section: Dichotomous Processesmentioning
confidence: 99%